THE IMPACT OF THE 2007–2009 FINANCIAL CRISIS ON RISK MANAGEMENT IN CREDIT INSTITUTIONS - Boda, Michał (Copernican Journal of Finance & Accounting, 2017)
Risk and risk management are a key aspect of the financial management of the bank. In the banking business since the mid-70s of the twentieth century, the risk continues to increase. The result of that excessive growth was the financial crisis in the years 2007–2009. Due to underestimation, lack of adequate and updated risk models, many financial institutions were on edge of bankruptcy due to insufficient funds needed to cover the losses. The financial crisis has highlighted many of the weaknesses of a regulatory nature in the functioning of the global financial system, especially the banking system. In order to reduce occurrence of future similar negative phenomena, the Basel Committee on Banking Supervision has decided to reform the banking system. As a result, Basel III was created. CRR Regulation and Directive CRD put particular emphasis on height of own funds and risk-weighted assets. All these have showed many weaknesses of the banking system, from which health and status is determined the whole economy. This paper will focus on the impact of the 2007–2009 financial crisis on risk management effectiveness in credit institutions. There will be presented the possibility of an integrated risk measurement and management. The most known methods of integrated assessment are RORAC and RAROC models, which are both used for the evaluation of the entire bank, as well as business units, or individual transactions. RORAC and RAROC models are the basic concepts of measuring the effectiveness of risk. There will be also discussed Hurdle rate and its potential impact on the economy.